10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundMalnutrition affects nearly half of patients in Canadian hospitals and is associated with increased complications, longer hospital stays, and higher mortality. Audits at an urban acute care hospital identified gaps in nutrition screening, oral intake monitoring, weight surveillance, and interdisciplinary coordination, highlighting the need for a structured, patient-centred nutrition care model.AimTo evaluate the patients eating and recovering (PEAR) model by assessing improvements in nutrition screening, oral intake monitoring, and weight surveillance; evaluating the feasibility and effectiveness of delegating supportive nutrition care tasks to dietitian assistants (DAs); and determining its impact on interdisciplinary collaboration and staff satisfaction.MethodsAn interdisciplinary team, including patient partners, developed PEAR to clarify roles, improve workflows, and integrate a DA into nutrition care. The DA collaborated with nurses and allied health staff to conduct nutrition screening, monitor oral intake and weight, and support mealtime care, including tray setup, food preferences, dental care, and positioning. A descriptive pre- and post-implementation evaluation examined changes in nutrition care processes, workflow feasibility, and staff perceptions.SummaryPEAR improved nutrition care processes. Nutrition screening increased from 9% to 49%, while monitoring of oral intake and weight became more consistent. The DA played a key role in identifying patients at risk of malnutrition and supporting reliable nutrition tracking. Staff reported clearer workflows, stronger interdisciplinary collaboration, and reduced workload pressures. PEAR also reduced food waste by 7.47 kg between pre- and post-implementation measurement days, demonstrating environmental and financial benefits while strengthening interdisciplinary nutrition care in an acute elderly care unit.